DPP-4 inhibitor improves learning and memory deficits and AD-like neurodegeneration by modulating the GLP-1 signaling. (October 2019) - Chen, Shuyi; Zhou, Mei; Sun, Jie; Guo, Ai; Fernando, Roger Lakmal; Chen, Yanlin; Peng, Peng; Zhao, Gang; Deng, Yanqiu
Abstract: Glucagon-like peptide-1 (GLP-1) signaling in the brain plays an important role in the regulation of glucose metabolism, which is impaired in Alzheimer's disease (AD). Here, we detected the GLP-1 and GLP-1 receptor (GLP-1R) in AD human brain and APP/PS1/Tau transgenic (3xTg) mice brain, finding that they were both decreased in AD human and mice brain. Enhanced GLP-1 exerts its protective effects on AD, however, this is rapidly degraded into inactivated metabolites by dipeptidyl peptidase-4 (DPP-4), resulting in its extremely short half-time. DPP-4 inhibitors, thus, was applied to improve the level of GLP-1 and GLP-1R expression in the hippocampus and cortex of AD mice brains. It is also protected learning and memory and synaptic proteins, increased the O-Glycosylation and decreased abnormal phosphorylation of tau and neurofilaments (NFs), degraded intercellular β-amyloid (Aβ) accumulation and alleviated neurodegeneration related to GLP-1 signaling pathway. Highlights: DPP-4 inhibitors enhanced the level of GLP-1 and GLP-1R and improved GLP-1 signaling pathway in mice brain. DPP-4 inhibitors alleviated AD-like neurodegeneration via GLP-1 signaling pathway. DPP-4 inhibitiors protected impaired learning and memory in APP/PS1/Tau triple transgenic mice.